Dancing with the gods: observations of the Niino Snow Festival - Graf, Tim; McMullen, Matthew D. (Bulletin of the Nanzan Institute for Religion & Culture, 2019)
The Niino Snow Festival is a three-day event that attracts visitors by combining traditional arts and prayer rituals for worldly benefits at a secluded local mountain shrine. Weathering the cold, fatigue, and the smoke of burning wood, participants engage in night-long dances with local gods in expectation of a bountiful harvest. The 2019 Nanzan Seminar comprised an excursion for attendants to witness the festival’s aesthetically pleasing yet ultimately challenging environmental setting and performances. It is within this context that we observed and learned how decreasing participation in the course of rural depopulation has changed the festival over time, raising questions as to how long it will survive in its current form.